The sustainable urban design handbook - Larco, Nicolas; Knudson, Kaarin (New York, NY : Routledge, 2023)
"With more than half of the world's population now living in urbanized areas and the threats of climate change and resource depletion becoming tangible, Sustainable Urban Design is quickly becoming a critical field. The Sustainable Urban Design Handbook gathers the best sustainability practices and latest research from the fields of architecture, landscape architecture, planning, development, ecology and environmental engineering and presents them in a graphically rich and easy to access format that is a resource for urban design projects of all scales. The book presents a comprehensive Sustainable Urban Design Framework that organizes the many elements of urban design in relation to four main resource targets: Transportation Based Energy Use, Water, Ecology and Habitat, and Non-Transportation Based Energy Use and Production and four key scales: Regional, Neighborhood/District, Street/Block, and Project/Parcel. The framework allows designers and planners to see the range of elements they should address in any given scale project as well as the related elements that exist at other scales. Each element is broken out in its own section that describes the element and its importance, compares typical practices and recommended approaches, explains the connection to other elements, and ends with a list of 'Rules of Thumb' that can be used to directly guide project work. Easy to use and reference, The Sustainable Urban Design Handbook provides both an in depth introduction to topics across sustainable urban design and serves as an on-going desktop reference for anyone involved in the creation of sustainable urban environments"--
Keywords: Municipal engineering -- Handbooks, manuals, etc; City planning -- Handbooks, manuals, etc; Sustainable urban development -- Handbooks, manuals, etc; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning